A Business Model Canvas untuk Pemberdayaan Desa Adat di Kabupaten Jember - Titisari, Purnamie; Sari Mahanani, Retno; Wahyu Lelly Hana Setyanti, Sri; Budi Susanto, Arnis (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This Community Service Program (PKM) aims to facilitate traditional villages in Jember Regency in designing, validating, and implementing sustainable business models. This business model is expected to increase the economic independence of the community while strengthening the preservation of cultural values ​​and local wisdom. The PKM program is implemented through lectures, technical guidance, and discussions. The material presented covers mapping village potential and assets, formulating unique selling points, identifying appropriate target markets, designing sustainable income streams, enhancing community capacity, and building strategic partnership networks for sustainability. The outcome of the PKM program is the creation of a creative economic ecosystem rooted in local culture. Traditional villages are no longer positioned as passive objects, but as empowered subjects (business actors) capable of managing their potential professionally and sustainably without losing their identity.